Early geomagnetic data from the Astronomical Observatory of Madrid (1879–1901). (19th November 2018) - Pro, Carmen; Vaquero, José M.; Merino‐Pizarro, Dámaris
Abstract: The recovery of early geomagnetic data is essential to improve knowledge of the evolution of the geomagnetic field. A recently recovered dataset is described that includes mean decadal (10 days) values of the geomagnetic declination and some disperse values of geomagnetic inclination measured at the Astronomical Observatory of Madrid from 1879 to 1901. These recovered data are compared directly with the results obtained from a geomagnetic model. The data have now been made accessible for the scientific community in digital form. Open Practices: This article has earned an Open Data badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available athttps://doi.pangaea.de/10.1594/PANGAEA.885886 . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .